Is land-use change a cause of loss of pedodiversity? The case of the Mazzarrone study area, Sicily - Lo Papa, Giuseppe; Palermo, Vanessa; Dazzi, Carmelo (Geomorphology, 2011)
Anthropogenic soils created ex novo by land-use change in large scale farming are, from a pedogenetic point of view, catastrophic events that bring the soils to time zero and change the natural pattern of the soilscape, remarkably, in some cases. The quantitative aspects of pedodiversity of a soilscape in South-East Sicily, where some types of soils, in recent decades, have suffered a consistent reduction due to the transformations by large scale farming, are considered. The evolution of pedodiversity over a 53-year period (1955 to 2008) is examined using a dedicated statistical method and a space–time model based on Markov analysis and cellular automata in order to predict the evolution of the soilscape pattern in the next 42 years (i.e. until 2050). Soil subgroups, using the USDA Soil Taxonomy and a classiﬁcation proposal, were considered and the following indices were used: richness; Shannon's diversity index; Simpson diversity index; modiﬁed Simpson's diversity index; Shannon's evenness index; Simpson's evenness index and modiﬁed Simpson's evenness index. These indices measured over time, show, quantitatively, a decrease in pedodiversity that highlights the effect of the human intervention in modifying the natural order of the soilscape.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Anthropogenic soils; Cellular automata; Markov analysis; Pedodiversity; Soil space–time modeling